How does climate change affect a fishable resource? The case of the royal sea cucumber (Parastichopus regalis) in the central Mediterranean Sea - Scannella, Danilo; Bono, Gioacchino; Di Lorenzo, Manfredi; Di Maio, Federico; Falsone, Fabio; Gancitano, Vita; Garofalo, Germana; Geraci, Michele Luca; Lauria, Valentina; Mancuso, Maria; Quattrocchi, Federico; Sardo, Giacomo; et al. (Frontiers in Marine Science, 2022)
Holothurians or sea cucumbers are key organisms in marine ecosystems that, by ingesting large quantities of sediments, provide important ecosystem services. Among them, Parastichopus regalis (Cuvier, 1817) is one of the living sea cucumbers in the Mediterranean actively fished for human consumption in Turkey, Greece and Spain, where it is considered a gastronomic delicacy. In the Strait of Sicily (central Mediterranean Sea) this species is not exploited for commercial uses even if is used as bait by longline fishery. Although the species is frequently caught by bottom trawling, since it is resistant to the air exposition at least in cold months and discarded at sea by fishers after catch, it is reasonably considered not affected by substantial fishing mortality. Having observed a strong decrease in abundances since 2018, possible effects of some ecological factors related to current climate change such as temperature and pH were sought. Generalized Additive Models (GAMs) have been applied to investigate the relationship among the abundance of P. regalis, environmental variables and fishing effort that are expected to affect its population dynamics. Long time series on species densities (2008-2021) have been extracted from the MEDITS bottom trawling survey and modelled as function of environmental parameters (i.e. salinity, dissolved oxygen, ammonium, pH and chlorophyll α) and fishing effort (i.e. total number of fishing days per gross tonnage). Our results showed that the species prefers the soft bottoms (50-200m) of the Adventure Bank and Malta Plateau, and its distribution changed over time with a rarefaction of spatial distribution and a slight deepening starting from 2017 and 2011, respectively. In addition, a positive relationship with pH concentration in surface waters during the larval dispersal phase (3-year lag before the survey) and nutrient concentration at sea bottom (1-year lag) has been found suggesting that this species is sensitive to climate change and food availability. This study adds new knowledge about the population dynamics of an unexploited stock of P. regalis under fishing impact and environmental drivers, highlighting the need of including the effect of environmental factors in implementation of management plans where the species is exploited by fisheries.